Sir Simon Rattle conducts Rimsky-Korsakov, Borodin and Mussorgsky - Borodin, Aleksandr Porfirʹevich 1833-1887; Borodin, Aleksandr Porfirʹevich 1833-1887; Mussorgsky, Modest Petrovich 1839-1881; Mussorgsky, Modest Petrovich 1839-1881; Shostakovich, Dmitriĭ Dmitrievich 1906-1975 (ZDF, 2008)
In 2007 The Berlin Philharmonic Orchestra and Simon Rattle celebrated the New Year with Russian music. Every year in Berlin, the ritual remains unchanged: The Berlin Philharmonic Orchestra celebrates the New Year with a particularly festive concert. In 2007, the orchestra's musical director, Simon Rattle, conducted the concert. For the celebration to be complete, powerful Russian music producing an immediate effect was chosen, among the pieces were universally acclaimed favorites: The Polovetsian Dances and the Second Symphony by Alexander Borodin, the prelude to the Khovanshchina and the very famous Pictures at an Exhibition by Modest Mussorgsky orchestrated by Maurice Ravel. Following in the footsteps of these two composers who belonged to the group "The Five" formed in Saint Petersburg in 1860 around Balakirev, was Dmitri Shostakovich, whose dance from the ballet The Golden Age Rattle gives as an encore and describes as "crazy music." The musicians from Berlin, whose reputation for excellence is firmly established, play these works with a pleasure that is clearly apparent
Keywords: Opéras; Orchestre, Musique d', arr; Symphonies; Orchestre, Musique d'; Suites (Orchestre); Ballets; Operas; Orchestral music; Orchestral music, Arranged; Suites (Orchestra); Operas -- Excerpts, Arranged; Operas -- Excerpts; Ballets -- Excerpts; Suites (Orchestra) -- Excerpts; Webcast; Internet videos; Vidéos sur Internet